Hydrological response of hydrographic sub-basins in the Piracicaba River Basin - Southeast Region of Brazil - Carvalho, Ana Claudia Pereira; Lorandi, Reinaldo; Lollo, José Augusto Di [UNESP]; Collares, Eduardo Goulart; Moschini, Luiz Eduardo (Editora da Universidade Federal de Uberlândia - EDUFU, 2022)
The use of water for several human needs, associated with climate change, indicates how important it is to understand the response of watersheds, in order to provide adequate planning and management of water resources. This study was carried out in two pairs of hydrographic watersheds, in the Piracicaba River Basin, southeast of Brazil, analyzing water response, integrating in-situ collected precipitation and flow data, natural environmental attributes, and anthropic environmental data. To support the analysis, Surface Runoff Potential Charts (SRPC) were made. The evaluation of the physical characteristics of the sub- watersheds (SW(A) and SW(B)) shows that these areas present very low to low potential, indicating greater infiltration capacity. The use and coverage of the soil partially justifyies flow changes in pair 1, since SW(A) has a larger extent of agricultural areas that can use irrigation. SW(B), even with a greater variety of crops, has a smaller cultivated area and tends to demand less water. As for pair 2, the low runoff potential was mainly due to the predominance of flat relief in the sub-basins. Their soils present a higher fraction of silt and clay, with thicknesses > 5m in SW(C) and varying from 0.5m, reaching depths above 5m in SW(D). The physical properties of these soils do not provide a low flow rate, but when associated with the low slope of the land, geological characteristics and low drainage density are configured in regions where the flow flows more slowly, contributing to the evaporation and infiltration process. The use and coverage of the soil also partially justifyies the flow oscillations, due to anthropic activities in SW(C) and SW(D), such as irrigation and spraying of citrus, fertirrigation of sugarcane, irrigation of seedling nurseries, directly interfering with the availability of surface water.
Keywords: Watershed; Flow; Water resource management; Rainfall; Runoff